2006
DOI: 10.1158/1078-0432.ccr-05-1986
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Antitumor Effect of Intratumoral Injection of Dendritic Cells in Combination with Local Photodynamic Therapy

Abstract: Purpose: Photodynamic therapy (PDT), which is used clinically for the palliative treatment of cancer, induces local tumor cell death but has no effect on tumors in untreated sites.The purpose of this study was to determine if local PDT followed by intratumoral injection of nai « ve dendritic cells (IT-DC) induces systemic antitumor immunity that can inhibit the growth of untreated as well as PDT + IT-DC^treated tumors. Experimental Design: BALB/c or C57Bl/6 mice were injected s.c. with CT26 colorectal carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 32 publications
6
51
0
Order By: Relevance
“…This study also revealed that the effect of this combined treatment is not limited to the treated tumour but is also effective in the control of distant growth. Similar results was published by Saji et al 72 with a combination of intratumourally injected DCs and ATX-S10 Na(II)-mediated PDT. They also observed a dramatic effect on both local and distant tumours.…”
Section: Specific Methodssupporting
confidence: 89%
“…This study also revealed that the effect of this combined treatment is not limited to the treated tumour but is also effective in the control of distant growth. Similar results was published by Saji et al 72 with a combination of intratumourally injected DCs and ATX-S10 Na(II)-mediated PDT. They also observed a dramatic effect on both local and distant tumours.…”
Section: Specific Methodssupporting
confidence: 89%
“…Although researches on the delivery system of photosensitizers have flourished in recent years, low enriching efficiency of photosensitizers still severely hamper the therapeutic effect of PDT. 15,16 In these researches, photosensitizer dose is always too large to guarantee the therapeutic effect in clinics, which increases potential phototoxicity to the normal tissues. Specificity and controllability of some photpsensitizers at the tumor site have been performed to improve retention; herein, we fabricated a novel magnetic mesoporous silica nanoparticle (MMSN) to deliver photosensitizer to the target site using the magnetic targeting technology.…”
mentioning
confidence: 99%
“…The potential of this synergy was corroborated using B16 tumor model, a poorly immunogenic and highly aggressive melanoma, with strong and durable tumor-specific results (Saji, Song et al 2006). …”
Section: Immune Stimulation Strategiesmentioning
confidence: 88%
“…ISPI not only exert a complete local response but also it was demonstrated the effective immune response against metastatic nodules. The immune response can also be stimulated by means of intratumoral injection of dendritic cells (DC), which combined with local photodynamic therapy induces a striking antitumor effect with potent systemic antitumor immunity (Saji, Song et al 2006). PDT creates the perfect microenvironment for tumor antigen acquisition and DCs activation, alleviating the need to do in vitro loading of DCs with tumor antigens.…”
Section: Immune Stimulation Strategiesmentioning
confidence: 99%